(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
The present study examined the cash flow forecasting knowledge among traders in the mile one market in River State, Nigeria. One hundred and seventeen retail and wholesale business enterprises conveniently selected from Mile One Market participated in the study. A self-developed instrument was used as a measure. The study adopted a cross-sectional survey design. The result was based on data from the study that adopted a cross-sectional survey design. The result was based on data from 38 (38%) food and beverages, 30 (30%) wearables, 16 (16%) beauty care, and 16 (16%) pharmaceuticals in mile 1 market. Data were evaluated using the statistical package for social sciences (SPSS, version 23). A simple percentage formula was used to analyze the data to determine cash flow knowledge among the respondents. The result indicated that 78 respondents, representing 66.7% of the total participants, scored high on cash flow knowledge, meaning they understand cash flow forecasting. The finding suggests that 39, representing 33.3% of the respondents, were not knowledgeable about cash flow forecasting. The result has implications for research and business analysis.